Evaluation of Polytomous Item Locations in Multicomponent Measuring Instruments: A Note on a Latent Variable Modeling Procedure. (June 2023) - Raykov, Tenko; Pusic, Martin
This note is concerned with evaluation of location parameters for polytomous items in multiple-component measuring instruments. A point and interval estimation procedure for these parameters is outlined that is developed within the framework of latent variable modeling. The method permits educational, behavioral, biomedical, and marketing researchers to quantify important aspects of the functioning of items with ordered multiple response options, which follow the popular graded response model. The procedure is routinely and readily applicable in empirical studies using widely circulated software and is illustrated with empirical data.